Electrostatic force-driven anchoring of Ni(OH)2 nanocrystallites on single-layer MoS2 for high-performance asymmetric hybrid supercapacitors. (10th October 2019) - Zhao, Chenyang; Wang, Renheng; Zhang, Youfang; Chen, Lunfeng; Li, Tingya; Deng, Xin; Zhang, Peixin; Lu, Xuehong
Abstract: The electrochemical performance of battery-type electrode materials is limited by their diffusive charge storage mechanism in supercapacitors, leading to sluggish electrode kinetics and capacity loss. In this article, we present an electrostatic-induced strategy and rational structural design as a feasible solution to solve this problem. Chemically exfoliated single-layer MoS2 with negative charges is used as the substrate for the confined growth of Ni(OH)2 . The electrostatic attraction between MoS2 and Ni 2+ results in homogeneous distribution of Ni 2+ and subsequent formation of ultrasmall Ni(OH)2 crystallites (∼5.5 nm). Due to the smaller size of Ni(OH)2 and synergetic effect between the components, the graphene coated Ni(OH)2 /MoS2 heterostructure (G-Ni(OH)2 /MoS2 ) exhibits a capacity as high as 890 C g −1 at 2 mV s −1, close to the theoretical capacity of Ni(OH)2 . Moreover, the rapid capacitive surface charge is found to account for 34% of the total charges, ensuring excellent high-rate and cycling performances. As a proof-of-concept demonstration, G-Ni(OH)2 /MoS2 is assembled into an asymmetric hybrid supercapacitors (AHSC) with active graphene as the counter electrode. The AHSC shows a power density of 3500 W kg −1 at 13 Wh kg −1 and stable cycling performance up to 4000 cycles. Graphical abstract: Image 1 Highlights: A G-Ni(OH)2 /MoS2 heterostructure is prepared via electrostatic-induced assembly. The charge storage behavior is adjusted by nanoscaling and heterostructuring. The G-Ni(OH)2 /MoS2 exhibits excellent high rate capabilities and cycling stability. This strategy opens a new avenue for the controllable synthesis of heterostructures.